Chandrabala Modi Academy, Ankleshwar (B) - Dixit, Mukund; Sharma, Rajeev (Of Indian Institute of Management, Ahmedabad) (London : Indian Institute of Management, Ahmedabad, 2006)
The Chandrabala Modi Academy (B) case has been written to discuss the role of the Leader. In this example the principal of Chandrabala Modi Academy Mr. Bhattacharya is used to stress the role of a leader as a reviewer and restrategiser. As a reviewer Mr. Battacharya is required to assess what has happened in the school thus far and develop guidelines for the future. As a restrategiser he is required to reformulate a strategy for the school in the context of past experience and possible developments in the future. The case stresses the need for a leader to develop a framework for reviewing the past activities and reformulating a strategy for the future.
Originally published in Dixit, M., & Sharma, R. (2006). Chandrabala Modi Academy, Ankleshwar (B). RJMC0002(B). Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chandrabala Modi Academy; Business planning; Strategic planning; Decision making; Industrial management